AKUNTABILITAS PEMERINTAH DAERAH DI MATA RAKYAT: STUDI TENTANG PERSEPSI MASYARAKAT TERHADAP KINERJA PEMERINTAH KABUPATEN PEMALANG - WIBOWO, MUKTI AGUNG (Politika: Jurnal Ilmu Politik, 2014)
In the era of democracy  where all of society have a freedom to do things that pertain to their needs. Through democracy , every society be eligible to get the protection and have their fundamental rights. The government district of Pemalang is one of the local government that cant be separated from the responsibility obligation to Pemalang society. Pemalang’s government has been doing efforts to provide services to the Pemalang society. Start from the development of health infrastructure, school, puskesmas, hospital and the general services like regulation, administration, and all of services that correlate with increasing life quality have been done through maksimal budgeting. But that is can’t be walk smoothly because financial problem and the limitation of human resources as a suppoort in the policy.  In this case, there’s a possibility between gap and expectation with the performance of Pemalang’s government. Society as a object of the policy taken by Pemalang’s government, sure they feel the policy that have been take by Pemalang’s government in the various sector. Of course, all of them has some level of expectation to government performance. Based on this assumptions so appearing a question about the perception of society against Pemalang’s government performance, level of satisfaction society against the public service function, development and  the general government, then about the expectation of society against the Pemalang’s government peerformance. Keyword : Public perception, Government of district performance, Government district of Pemalang.